Controlador adaptativo robusto por modelo de referência no eixo zero aplicado ao controle de desbalanço de tensões de fase em geradores de indução autoexcitados isolados - Gentile, Francisco Ramon (2020)
In this work, a voltage and frequency regulation system was implemented for a micro hidropower generation plant using an induction generator operating in standalone mode or not connected to a commercial energy distribution network. The selection of the induction generator is since for low powers it presents advantages compared to a synchronous generator of the same power. The studied micro-generation system has a primary engine that simulates an uncontrolled turbine and delivers relatively constant power, coupled to the generator, bank of excitation capacitors, the DSTATCOM and the consumption loads. The development consisted in generating the appropriate control loops for a reactive power compensation device, known as DSTATCOM, which is the arrangement that performs the voltage and frequency compensation by handling the flow of reactive and active power respectively. These control loops were implemented in a digital signal processor, in synchronous dq0 coordinates, which allows the use of classic fixed-gain PI compensators, for the control of the variables of interest, except for the case of phase voltage unbalance regulation where an Reference Model Robust Adaptive Controller (RMRAC) was used, in order to check if its use is feasible. This work aims to present the design of a RMRAC used in the zero axis voltage loop of the rotating synchronous reference frame to perform the control of phase voltage unbalance, as well as current harmonic compensation. Simulated and experimental results obtained demonstrate the feasibility of the idea for voltage unbalance compensation. But above all, it opens the way to continue with the study and improvement of this project.